TWO HUNDRED YEARS OF THE THEORY OF HISTORIOGRAPHY IN LITHUANIA, OR HOW JOACHIM LELEWEL DID BECOME THE PIONEER OF MODERN COMPARATIVE HISTORY - Norkus, Zenonas (Sociologija. Mintis ir veiksmas, 2016)
In 1815 distinguished Polish historian Joachim Lelewel (1786–1861) published in Vilnius his Historyka, marking the origin of the theory of historiography in Lithuania and Poland. This paper, originally presented at the international conference at Vilnius university in November 2015 to celebrate 200-year anniversary of this event, explores the evolution and original features of Lelewel’s views on writing history. Main focus is on the relation between his methodological and substantive work: did Lelewel’s huge time and effort input into methodological reflection did pay off, endowing him with the competitive advantages in the “doing history”? The author argues that Lelewel’s unconventional idea of the essential unity of history and statistics did help him to conceive his pioneering comparison of Poland and Spain in 16–18th centuries. Tabular form of presentation and implicit use of the multilateral multivariate comparisons can be attributed to Lelewel’s dual institutional role of the professor of universal history and of statistics at Vilnius university in 1822–1824. Lelewel’s unconventional conception of the relation between historical studies and statistics is another expression of this dualism. Another source of Lelewel’s inspiration as comparativist is Plutarch’s “Parallel Lives”.
Keywords: Joachim Lelewel; theory of historiography (historics); philosophy of history; comparative history; statistics; Plutarch